PENGGUNAAN MEDIA PEMBELAJARAN QUARTET CARD UNTUK MENINGKATKAN PROSES DAN HASIL BELAJAR PENDIDIKAN PANCASILA MATERI KERAGAMAN BUDAYA INDONESIA KELAS V UPTD SD NEGERI 142 BARRU - Ritha Tuken; Shasliani, Shasliani; Amanda, Ayu (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The problem studied in this study is the low literacy issues of Pancasila Education in class V UPTD SD Negeri 142 Barru. This study aims to describe the use of Quintet Card literacy media in perfecting learning issues of Pancasila Education on the material of Indonesian Cultural Diversity in the class. This exploration uses a qualitative approach and the type of exploration used is Classroom Action Research (PTK) which is cyclical, this exploration includes the stages of planning, perpetration, observation, and reflection. The main focus of this exploration is to find out how the process and literacy issues of Pancasila Education using Quintet Card literacy media. The subjects in this study involved preceptors and 19 scholars of class V UPTD SD Negeri 142 Barru in the indeed semester of the2023/2024 academy time, conforming of 12 boys and 7 girls. The data collection ways used were observation, tests, and attestation. Data were anatomized through data collection, data reduction, data donation, and conclusion delineation. The results showed an increase from cycle I to cycle II, where the test results increased from the qualification" Less" in cycle I to" Good" in cycle II. therefore, it can be concluded that the use of Quintet Card literacy media is effective in perfecting learning issues of Pancasila Education on the material of Indonesian artistic diversity for class V scholars of UPTD SD Negeri 142 Barru.